Impact of pretreatment and drying on the chemical composition and sensory quality of fried yam (Dioscorea rotundata) chips - Evans Ntim Amedor; Frederick Sarpong; Paa Kwesi Bordoh; Evans Frimpong Boateng; James Owusu-Kwarteng (Exploration of Foods and Foodomics)
Aim: This study examined the combined effects of pretreatment methods (blanching, citric acid, and ascorbic acid) and oven drying on the chemical composition and sensory quality of fried yam (Dioscorea rotundata) chips, aimed at optimizing processing conditions for improved product quality. Methods: Fresh yam slices were subjected to three pretreatment conditions: blanching (4 min at 100°C), a 5% citric acid solution, and a 1% ascorbic acid solution, compared to the untreated samples (control). All samples underwent convective drying at 80°C with an air velocity of 2.0 m/s. The proximate composition and mineral content of the dried samples were evaluated using official methods of food analysis and atomic absorption spectroscopy, respectively, while the color parameters and sensory evaluations of the fried yam chips were conducted using a colorimeter and a nine-point hedonic scale. Results: Both pretreatment and drying significantly (p < 0.05) influenced mineral content in the dried yam chips. In comparison to the control, all proximate constituents decreased after drying, except for carbohydrates, which increased in the dried pre-treated samples. The fried samples of yam chips that had been blanched for 4 min received higher acceptability scores for taste, color, crispiness, and overall acceptability on the sensory scale, compared to samples pre-treated with 1% ascorbic acid and 5% citric acid. However, the acid pre-treated samples demonstrated the least browning effect in the fried products. Conclusions: The processes of pretreatment and drying significantly modified both the mineral and proximate composition of the yam chips, increasing carbohydrates while other components decreased post-processing. Blanched samples exhibited superior sensory acceptability across all attributes, while the acid pretreatments effectively reduced browning in the final fried products.